Diseño e implementación de una red de microondas y radiocomunicación en VHF como fortalecimiento de la red de apoyo comunitaria de la zona Metropolitana de Tunja (2021)
The Tunja's Metropolitan Police - METUN is the public entity in charge of strengthening the security and citizen coexistence. To do this, they have a communitary support network that provides its services in the metropolitan area of Tunja, through radio communication systems. These systems use analog technology, which is considered to be obsolete, and therefore, it is necessary to migrate to a digital technology that allows to improve communication between the municipalities that make up such an area. To perform the technological conversion from analog to digital, it is designed and implemented a VHF system and by microwave using the available communications equipment, previously acquired by the Boyacá Government and the Tunja's Metropolitan Police.